A Comparison of the outcomes of two rehabilitation protocols after flexor tendon repair of the hand at Chris Hani Baragwanath Academic Hospital - Van Velze, Corrianne A. (University of Pretoria, 2017)
Dissertation (MOccupational Therapy)--University of Pretoria, 2017.